Pengaruh Penggunaan Pasir Puger Sebagai Agregat Halus Terhadap Karakteristik (LASTON AC-WC) - Hamdani Nugroho Hamdani; Mirza Gulam Rifqi; M. Shofiul Amin (Journal of Applied Civil Engineering and Infrastructure Technology, 2020)
Asphalt concrete is a layer in the construction of highway pavement consisting of fine aggregate, coarse aggregate, filler, and asphalt. asphalt has several advantages compared to other materials. Therefore concrete asphalt is widely used and its needs have increased. To complement these needs, research is conducted as an alternative that is using Puger sand as fine aggregate. Puger sand is natural sand containing iron ore of approximately 49.7% and has a reserve of concentrate of approximately 700,000 tons. The purpose of this research was to determine the use of Puger sand as fine aggregate on the characteristics of Laston AC-WC. This study uses 5 variations including 100%, 75%, 50%, 25% and 0% Puger sand mixture and using asphalt content of 5%, 5.5%, 6%, 6.5% and 7%. Marshall test results that have been done produce an optimum asphalt content of 5.5% with a variation of the use of a 50% Puger sand mixture. Obtained stability 1763.54 kg, Flow 3.7 mm, MQ 474.5 kg / mm, VIM 4.14%, VMA 15.2%, and VFB of 72.46%. So that the use of Puger sand as fine aggregate can complement the Bina Marga General Specifications 2018.